2015
DOI: 10.1590/s0102-865020150090000005
|View full text |Cite
|
Sign up to set email alerts
|

The influence of low-level laser irradiation on spinal cord injuries following ischemia- reperfusion in rats

Abstract: PURPOSE:To investigate if low level laser therapy (LLLT) can decrease spinal cord injuries after temporary induced spinal cord ischemia-reperfusion in rats because of its anti-inflammatory effects. METHODS:Forty eight rats were randomized into two study groups of 24 rats each. In group I, ischemic-reperfusion (I-R) injury was induced without any treatment. Group II, was irradiated four times about 20 minutes for the following three days. The lesion site directly was irradiated transcutaneously to the spinal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…670 nm treatment has shown to significantly reduce neuronal cell death following SCI from 1-dpi. A similar study using 810 nm treatment showed 50% less motor neuron death following ischemia-induced SCI at 3-dpi 60 . The mechanism by which 670 nm treatment reduces neuronal cell death might be related to reduced iNOS ( Fig 9 ).…”
Section: Discussionmentioning
confidence: 71%
“…670 nm treatment has shown to significantly reduce neuronal cell death following SCI from 1-dpi. A similar study using 810 nm treatment showed 50% less motor neuron death following ischemia-induced SCI at 3-dpi 60 . The mechanism by which 670 nm treatment reduces neuronal cell death might be related to reduced iNOS ( Fig 9 ).…”
Section: Discussionmentioning
confidence: 71%
“…All rats were deeply anesthetized with sodium pentobarbital (25 mg/kg) and perfused with saline. Spinal cord sections from the tenth thoracic segment were dissected totally and fixed in 10% formalin and embedded in paraffin using routine procedures 37 . Serial transverse sections (5 μm) were cut from paraffin blocks and stained with HE for histopathologic examination under a light microscope (Leica DM4000 M, Wetzlar, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental data have suggested nervous tissue regeneration by laser-induced photobiomodulation in neurons. In fact, a low-power infrared (810 nm) laser was able to promote axonal regeneration and functional recovery in rats affected by spinal cord injury caused by different types of trauma in experimental models [92][93][94][95]. Also, mechanisms of Ca 2+dependent BDNF mRNA transcription could be triggered by exposure to a low-power red (632,8 nm) laser in primary neuron cultures from rat spinal cord [96].…”
Section: Could Low-power Lasers Be Effective On Amblyopic Eyes?mentioning
confidence: 99%